Phytochemical profile and free radical scavenging activity of Entada spiralis stem bark - Opeyemi Roheem, Fatimah; Mat So'ad, Siti Zaiton; Ahmed, Qamar Uddin; Jamal, Parveen; Mohd Hassan, Norazian (2016)
Entada spiralis Ridl. (family leguminosae) is a woody climber known to possess a wide range of ethnomedicinal properties. This study reports the phytochemical components of different extracts and its free radical scavenging activity. Both polar and non polar extracts were screened for their phytoconstituents. Free radical scavenging activity was measured using 2,2 diphenyl-picrlhydrazyl (DPPH). Phytoconstituents of these extracts were observed in decreasing order from MeOH > CHCl3 > Et2O. All the extracts showed radical scavenging activity in a concentration dependent manner. Percentage inhibitory activity of MeOH was observed to be higher (77.83 ± 0.64 ) than CHCl3 and Et2O extracts (48.76 ± 1.24, 20.27 ± 4.05 respectively